Use of aspirin as sole oral antiplatelet therapy in acute flow diversion for ruptured dissecting aneurysms. (21st September 2016) - Chiu, Albert Ho Yuen; Ramesh, Rajalakshmi; Wenderoth, Jason; Davies, Mark; Cheung, Andrew
Abstract : Subarachnoid hemorrhage secondary to rupture of a circumferential dissecting aneurysm continues to be a treatment dilemma. Vessel sacrifice, when possible, continues to be the safest option but in certain cases this is not possible due to lack of collateral supply. In such cases, coil assisted endovascular flow diversion has become a potential option but the requirement for dual antiplatelet therapy in an unsecured intracranial aneurysm continues to raise concern. We present a 48-year-old man with a World Federation of Neurological Surgeons grade 5 subarachnoid hemorrhage, secondary to a ruptured intradural left vertebral artery dissecting aneurysm, who was treated successfully with a pipeline embolization device with Shield technology using aspirin and a single intravenous loading dose of abciximab. To our knowledge, this is the first case of an acute flow diversion performed using only aspirin as the sole oral antiplatelet agent.